2014
DOI: 10.4323/rjlm.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of crania in a Romanian population: Discriminant function analysis approach for sex estimation

Abstract: Regarding sex estimation on human skeletal remains, the current trend in forensic anthropology is towards creating national standards, as population-specificity of discriminant functions is now a known fact. Also, over the last period of time, discriminant function analysis of osteometric data has become the method of choice in forensic anthropology, as it renders high accuracy results, superior to those obtained by visual shape assessment or direct metric comparison. We have conducted a study on 200 adult cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…The mandible is one of the most resistant bones with high preservation rates in various environments. Although sex estimation methods based on the cranium are currently increasing in the Balkan Peninsula [11][12][13] the published studies on the mandible are restricted to archaeological populations [14], thus, without any forensic value.…”
Section: Discussionmentioning
confidence: 99%
“…The mandible is one of the most resistant bones with high preservation rates in various environments. Although sex estimation methods based on the cranium are currently increasing in the Balkan Peninsula [11][12][13] the published studies on the mandible are restricted to archaeological populations [14], thus, without any forensic value.…”
Section: Discussionmentioning
confidence: 99%
“…In present study this index showed a sexual difference without temporal variation (contemporary vs subrecent). Gabel [46] [73] and Romanian (M/F:57.78/57.16) [72]. It is also observed that the values may not always be greater in males.…”
Section: Transverse Craniofacial Indexmentioning
confidence: 99%
“…The study established a sex determination accuracy based on these 2 variables of 80% for men and 69.2% for women, concluding that the measurements are significantly higher in men rather than women [55]. Rossi [56], Marinescu [57] and Nitek [58] reached the same conclusions.…”
Section: Anthropometrymentioning
confidence: 69%